A Fox in the Land of Ulro: Miłosz and Beckett - Kopciński, Jacek (Colloquia Litteraria, 2019)
In the sketch I present Beckett as a representative of western civilisation and a dialogue between Beckett and Czesław Miłosz. A characteristic outcome of this confrontation are the instruction for the habitués of the Urlo Land (Ziemia Urlo): cultivation of love for order, exercising the memory against the flow of time, choice of goodness despite the unmitigated evil, faith in what is visible, love for facts and search for meaning.